Pengaruh Training dan Work Facilities terhadap Employee Performance Melalui Work Disiplin sebagai Variabel Intervening pada PT Semen Padang - Wahyu Nisa Oktavia; Yamasitha Yamasitha; Chintya Ones Charli (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to determine the influence of training and work facilities on employee performance through work discipline as an intervening variable in PT Semen Padang. The method of collecting data is through surveys and distributing questionnaires to employees as respondents using a quantitative approach. The data analysis technique used is structural Equation Modeling (SEM) analysis with Partial Least Square (PLS) 3.0.The results of the study show that there is a positive and insignificant influence between work facilities on employee performance through work discipline at PT Semen Padang. There is a positive and significant influence between training and work discipline. There is a positive and significant influence between work facilities on work discipline at PT Semen Padang.There is a positive and significant influence between training on employee performance at PT Semen Padang. There is a positive and significant influence between work discipline on employee performance at PT Semen Padang. Training has a positive effect and mediates work discipline on employee performance.